Acute effects of intense interval training on running mechanics - Collins, M. H.; Pearsall, D. J.; Zavorsky, G. S.; Bateni, H.; Turcotte, R. A.; Montgomery, D. L. (Journal of Sports Sciences, 2000)
The aims of this study were to determine if there are significant kinematic changes in running pattern after intense interval workouts, whether duration of recovery affects running kinematics, and whether changes in running economy are related to changes in running kinematics. Seven highly trained male endurance runners (VO2max = 72.3 +/- 3.3 ml kg-1 min-1; mean +/- s) performed three interval running workouts of 10 X 400 m at a speed of 5.94 +/- 0.19 m s-1 (356 +/- 11.2 m min-1) with a minimum of 4 days recovery between runs. Recovery of 60, 120 or 180 s between each 400 m repetition was assigned at random. Before and after each workout, running economy and several kinematic variables were measured at speeds of 3.33 and 4.47 m s-1 (200 and 268 m min-1). Speed was found to have a significant effect on shank angle, knee velocity and stride length (P < 0.05). Correlations between changes pre- and post-test for VO2 (ml kg-1 min-1) and several kinematic variables were not significant (P > 0.05) at both speeds. In general, duration of recovery was not found to adversely affect running economy or the kinematic variables assessed, possibly because of intra-individual adaptations to fatigue.